Examining the Experiences of a Short Break Scheme amongst Adolescents with Disabilities (Service Users) and their Parents. Issue 2 (4th March 2018) - Spruin, Elizabeth; Abbott, Nicola; Holt, Nicole
Abstract: Globally, families who care for a child or adolescent with disabilities have been found to experience high levels of maternal ill health, stress, depression and family breakdown. In extreme cases, children and adolescents may have to move away from their family to a permanent residential placement. A potentially more appropriate and cost-effective approach is the provision of family support services; predominantly these have taken the form of short break schemes, whereby temporary (respite) care is issued to provide short-term relief for the family (e.g. regular afternoon care). This research reported the impact of a short break scheme from the perspective of the service users and their parents by conducting interviews with adolescents with disabilities and quantitative questionnaires with the parents, following a summer short break scheme.